2021
DOI: 10.1097/jcma.0000000000000585
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning for abdominal ultrasound: A computer-aided diagnostic system for the severity of fatty liver

Abstract: Background: The prevalence of nonalcoholic fatty liver disease is increasing over time worldwide, with similar trends to those of diabetes and obesity. A liver biopsy, the gold standard of diagnosis, is not favored due to its invasiveness. Meanwhile, noninvasive evaluation methods of fatty liver are still either very expensive or demonstrate poor diagnostic performances, thus, limiting their applications. We developed neural network–based models to assess fatty liver and classify the severity using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Table 4 compares machine learning algorithms for liver disease diagnosis [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. In the current study, a high level of diagnostic performance was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Table 4 compares machine learning algorithms for liver disease diagnosis [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. In the current study, a high level of diagnostic performance was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Morbidity from DM is mainly secondary to microvascular damage and dysfunction (hypertension, retinopathy, nephropathy, neuropathy, diabetic foot, and nonalcoholic fatty liver), macrovascular injury and occlusion (hypertension, atherosclerotic cardiovascular disease), and acute complications of life-threatening diseases, including hyperglycemia (hyperglycemia hyperosmolar nonketotic coma and diabetic ketoacidosis) or hypoglycemia. [52][53][54][55][56][57][58][59][60][61][62] DM is also a main cause of end-stage of renal disease (ESRD or kidney failure), lower-extremity amputation, and blindness. All DM-related loss of vital and nonvital organ functions contribute to significant impairment of normal daily activity and dramatic deterioration of quality of life (QoL) in DM.…”
Section: Type 2 Diabetes Mellitus and Morbidities Or Concomitant Como...mentioning
confidence: 99%
“…CT and MRI or ultrasound are commonly administered screening modalities for various abdominal diseases both emergent or chronic ( Tanaka et al, 2006 ). This location of imaging harbors indicators including visceral fat, hepatic steatosis, and skeleton muscle, which are closely related to MetS ( Lin et al, 2021a ; Chou et al, 2021 ; Pickhardt et al, 2021 ; Wu and Park, 2021 ). Machine learning, especially deep learning methods, has been studied for fast automated quantification of different fat compartments, level of steatosis, and fat distribution ( Sun et al, 2020 ; Bhanu et al, 2021 ; Rhyou and Yoo, 2021 ).…”
Section: Early Detection Of Mets: From “Omics” To Clinical “Big Data”...mentioning
confidence: 99%